Simulation Analysis of Stress Corrosion of H62 Copper Alloy. Issue 6 (January 2021) - Dazhao, Yu; Tong, Zhang; Wentao, Niu
Abstract: H62 copper alloy is a commonly used material in engineering, and stress cracking of copper alloys has always been concerned. In this paper, a two-dimensional model of H62 copper alloy was established by COMSOL electrochemical module, and the stress corrosion of H62 copper alloy was analyzed by using measured engineering stress-strain curve. The results show that the tensile stress has a serious effect on the stress corrosion, and the excessive tensile stress will lead to the fracture failure of the contact.